The Incidence Of Recurrent Laryngeal Nerve Injury During Thyroid Surgery - Hindosh, Laith; Alnasr, Mumtaz; Rassam, Raid E. (AL-Kindy College Medical Journal, 2011)
Background: Recurrent laryngeal nerve injury is an important post-thyroidectomy complication for which different modalities of treatment were practiced to lower its incidence. Objectives: To estimate the incidence of recurrent laryngeal nerve injury in thyroid surgeries in relation to type of surgery, type of gland diseases & nerve identification. Methods: Different types of goiters prepared preoperatively by indirect laryngoscopy, operated upon with different types of surgeries, postoperative direct laryngoscopy by the anaesthetist were done and indirect laryngoscopy done as needed. Results: Of of 200 patients, the overall incidence of recurrent laryngeal nerve injury was 9 Patients (4.5%), 7 patients (77.8%) were unilateral nerve injury & 2 patients (22.2%) were bilateral nerve injury. The percent of temporary nerve injury was 8 patients (88.89%) & permanent injury 1 patient (11.11%).the incidence of injury in females was (4.57%) & in males was (4%). Injury was 1 patient out of 13 (7.69%) in total thyroidectomy, 1 patient out of 11 (9.09%) in completion thyroidectomy. Injury in malignant goiter was 2 patients (10%).finally it was higher if nerve was not identified (6.15%) than if identified (1.42%). Conclusion: Recurrent laryngeal nerve injury is more in malignant goiters, in more extensive surgery & if peroperative nerve identification was not practiced.